Inverting suprastomal granulomas. (20th June 2017) - Schweiger, Cláudia; Hart, Catherine K.; Cotton, Robin T.; Rutter, Michael J.
Abstract : Although suprastomal granulomas are a common complication of tracheotomy, they usually are an incidental finding and do not always require treatment. However, large granulomas may require removal, either to assist with speech production or to make the airway safer in the event of an accidental decannulation. Very large suprastomal granulomas extending up to or even through the vocal cords have been described. However, inverting suprastomal granulomas extending distally down the length of a tracheotomy tube have not been previously described. We present two cases of large suprastomal granulomas that extended distally down the trachea. Both extended beyond the tip of the tracheotomy tube, causing partial airway obstruction, and therefore required excision. Laryngoscope, 127:2883–2885, 2017